Thermal effects due to harmonics on dry-type transformers: Impact of filters and phase angles - Mateus Caruso Costa; Marcio Zamboti Fortes; Guilherme Gonçalves Sotelo; Bruno Wanderley França (Measurement: Energy)
Integrating distributed energy sources has introduced significant challenges to power quality. One notable issue is the generation of harmonic distortions by power electronics converters, which significantly affect the performance and efficiency of power transformers, leading to overheating and related adverse effects. Traditional metrics for non-sinusoidal currents, such as Total Harmonic Distortion (THD), Harmonic Loss Factor, and K-Factor, do not account for the phase angles of harmonic components. This paper evaluates the steady-state temperature of a dry-type transformer under different current conditions, emphasizing the impact of harmonic amplitudes and phase angles. Typical photovoltaic waveforms were applied experimentally to a custom dry-type transformer. Results demonstrated a temperature increase of up to 35% in harmonic cases, with a 7.9% variation observed between in-phase and out-of-phase harmonics of the same amplitudes. These findings highlight that harmonic phase angles can significantly influence transformer thermal behavior, underscoring the necessity of considering both harmonic amplitude and phase angles for a more accurate evaluation of transformer performance under non-linear loads.